The Mystical Imprint in the Poetry of Unamuno. Issue 7 (July 2017) - Longhurst, C. A.
Abstract : Unamuno's interest in the writings of Christian mystics is attested by his references to a large number of them in his philosophical essays, not only well-known Spanish mystics but also a number of Central European ones. Unamuno's quasipantheism – apparent at times in Del sentimiento trágico de la vida (1912), among other works – is almost certainly derived from the mystics, but it is in his poetry that his incursions into the mystical tradition have left their deepest imprint. This essay seeks to establish the important influence of mysticism on Unamuno by examining a number of themes frequent among mystical writers that make repeated appearances in his poetry: the longing for gnostic insight, the experience of states of barrenness, the use of metaphors such as light/darkness or presence/absence, the notion of nothingness, the problem of ineffability, and the ever-present danger of the loss of individuality.